Development, validation, and application of a method for the GC-MS analysis of fipronil and three of its degradation products in samples of water, soil, and sediment - Toffoli, Ana L. de[UNESP]; Mata, Kamilla da[UNESP]; Bisinoti, Márcia C. [UNESP]; Moreira, Altair B. [UNESP] (Taylor & Francis, 2015)
A method for the identification and quantification of pesticide residues in water, soil, and sediment samples has been developed, validated, and applied for the analysis of real samples. The specificity was determined by the retention time and the confirmation and quantification of analyte ions. Linearity was demonstrated over the concentration range of 20 to 120 µg L(-1), and the correlation coefficients varied between 0.979 and 0.996, depending on the analytes. The recovery rates for all analytes in the studied matrix were between 86% and 112%. The intermediate precision and repeatability were determined at three concentration levels (40, 80, and 120 µg L(-1)), with the relative standard deviation for the intermediate precision between 1% and 5.3% and the repeatability varying between 2% and 13.4% for individual analytes. The limits of detection and quantification for fipronil, fipronil sulfide, fipronil-sulfone, and fipronil-desulfinyl were 6.2, 3.0, 6.6, and 4.0 ng L(-1) and 20.4, 9.0, 21.6, and 13.0 ng L(-1), respectively. The method developed was used in water, soil, and sediment samples containing 2.1 mg L(-1) and 1.2% and 5.3% of carbon, respectively. The recovery of pesticides in the environmental matrices varied from 88.26 to 109.63% for the lowest fortification level (40 and 100 µg kg(-1)), from 91.17 to 110.18% for the intermediate level (80 and 200 µg kg(-1)), and from 89.09 to 109.82% for the highest fortification level (120 and 300 µg kg(-1)). The relative standard deviation for the recovery of pesticides was under 15%.
Keywords: Environmental matrices; Spe; Pesticides; Pyrazol